Penerapan Kurikulum Merdeka Belajar Pada Lembaga Pendidikan Islam Madrasah - Nurhamidin, Candra Puspita; Pateda, Lamsike (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The Independent Learning Curriculum is a significant initiative in education designed to provide greater flexibility for educators and students during the learning process. The implementation of this curriculum is expected to increase student engagement and improve the overall quality of education. This research aims to examine how the Kurikulum Merdeka Belajar is applied in Islamic secondary educational institutions, such as MTs Al-Ikhwan, and to evaluate its impact on the teaching and learning process. The issues addressed in this study include the methods of implementing the Kurikulum Merdeka Belajar, the factors influencing its success, the challenges or obstacles encountered, and the perspectives of teachers and students regarding the changes that have occurred. The approach used in this research is qualitative, employing a case study method. Data was collected through in-depth interviews with teachers, students, and parents, as well as direct observation of learning activities. The research findings indicate that the implementation of the Kurikulum Merdeka Belajar in Islamic secondary educational institutions has yielded positive results, with teachers feeling more freedom in designing lessons and students showing increased motivation. This study demonstrates that the Kurikulum Merdeka Belajar has great potential to enhance the quality of learning in Islamic secondary educational institutions. However, its success largely depends on supporting factors such as teacher training, infrastructure, and the integration of Islamic values. The implications of these findings can serve as a foundation for developing more innovative, inclusive, and relevant educational practices that meet the demands of the times. Overall, the Kurikulum Merdeka Belajar holds significant potential to improve the quality of education in Islamic secondary educational institutions. With appropriate support from schools and policymakers, existing challenges can be overcome.